The overnight guest [large type] - Gudenkauf, Heather (Thorndike Press large print basic series., 2022)
True crime writer Wylie Lark, snowed in at an isolated farmhouse where she's retreated to write her new book, finds a small child in the snow outside and, bringing him inside for warmth and safety, learns that the farmhouse isn't as isolated as she thought.